Historical Biogeography of a Clade of Liolaemus (Iguania: Liolaemidae) based on ancestral areas and dispersal-vicariance analysis (DIVA) - Díaz Gómez, Juan Manuel; Lobo, Fernando (Papéis Avulsos de Zoologia, 2006)
Although many phylogenetic studies have been made on the genus Liolaemus, they are inappropriate for a biogeographic study because of incomplete taxon sampling. Here we develop a biogeographic analysis using a new phylogenetic study of the chiliensis group, which differs from the other studies in having his members fully represented. The biogeographic analysis presented here consists in reconstructing the ancestral area of this clade, under three different methods of analysis: Fitch Optimisation, Dispersal Vicariance Analysis and Weighted Ancestral Area Analysis. The analyses were made on phylogenies from parsimony under equally weighted characters, as well as under implied weighting. The equally weighted tree recovers most of the groupings proposed in previous studies. The strict consensus of the implied weighting trees recovers fifteen groups, but there is no agreement of the relationships between those groups. The ancestral area analyses agree in an Andean-Patagonian origin for the chiliensis clade, and are congruent with previous hypotheses and paleontological data.